Responsabilidade tributária dos dirigentes de clubes associativos e dos administradores de SAFs - Góngora, Paloma Nunes (2024)
The objective of this work is to analyze the construction of the legal norm based on the wording of article 135, III, of the CTN in the hypothesis of attribution of tax liability to the directors of football clubs – known as non-profit association (associative clubs) – and to SAF administrators. In the end, it is concluded (i) that the concept of director/administrator corresponds to any natural person responsible for making decisions and conducting the activities described in the corporate purpose of the legal entity; (ii) due to the need to prove intent, excluding the mere existence of serious guilt; (iii) that the effects arising from the constitution of the third-party liability rule generate a hypothesis of subsidiarity; (iv) only the configuration of irregular management can give rise to third-party tax liability, excluding reckless management; (v) SAF administrators may be held responsible for the tax debts of the associative club in the event of SAF formation through partial spin-off or drop-down of assets in certain specific hypotheses; (vi) the status of limitations must be observed for the attribution of tax liability based on article 135, III, of the CTN, depending on the moment of incidence of the aforementioned rule. que deve ser observado o prazo decadencial e prescricional para a imputação de responsabilidade tributária amparada no artigo 135, III, do CTN, conforme o momento de incidência da referida norma